A comprehensive review of blockchain applications in industrial Internet of Things and supply chain systems. (3rd May 2021) - Malik, Nida; Alkhatib, Khalid; Sun, Yufei; Knight, Elijah; Jararweh, Yaser
Abstract: The industrial Internet of Things (IIoT) and supply chain systems have become one of the most important technologies to positively impact our daily life activities. Blockchain technology has recently gained popularity and it is increasingly being employed in a large number of applications and industries. The use cases for blockchain are growing rapidly in different fields and domains. Combining blockchain into IIoT and in our supply chain logistics could provide many solutions to the critical issues that current systems face today. Blockchain features such as immutability, decentralization, and data encryption are useful in solving the shortcomings of IIoT and the current supply chain systems security and integrity. This article presents a comprehensive review of blockchain applications in IIoT and supply chain systems. This article also focuses on the security aspects of blockchain integration within industry applications with the support of the emerging edge computing technology.